Semi-Coarsening in Multigrid Solution of Steady Incompressible Navier-Stokes Equations (Journal of Computational Mathematics, 1990)
We present a semi-coarsening procedure, i.e., coarsening in one space direction, to improve the convergence rate of the multigrid solver presented in [5] for solving the 2D steady Navier-Stokes in primitive variables when the aspect ratio of grid cells is not equal to 1, i.e., when $h_x/h_y \gg 1 \ {\rm or} \ll 1$, where $h_x$ is the grid step in $x$ direction and $h_y$ is the grid step in $y$ direction, $x$ and $y$ represent the Cartesian coordinates.